Investor Reaction to Disclosure of Past Performance and Future Plans - Emett, Scott A. (The Accounting Review, 2019)
ABSTRACT I examine how and why current-period performance shapes investors' evaluations of future-oriented disclosures. Three experiments provide evidence that a firm's current-period performance shapes investors' beliefs about the appropriateness of managerial optimism, which, in turn, affects investors' evaluation of firms that focus on either challenges or opportunities in future-oriented disclosures. When a firm is performing poorly, investors believe that managers can best achieve success by being optimistic about the future and, therefore, invest more when the firm focuses on opportunities rather than challenges in future-oriented disclosures. When a firm is performing well, on the other hand, investors believe that managers can best achieve success by being realistic about the future and, therefore, invest more when the firm focuses on challenges rather than opportunities.